2015
DOI: 10.1128/mcb.00286-15
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidic Acid Increases Epidermal Growth Factor Receptor Expression by Stabilizing mRNA Decay and by Inhibiting Lysosomal and Proteasomal Degradation of the Internalized Receptor

Abstract: Overexpression of epidermal growth factor receptor (EGFR) is one of the frequent mechanisms implicated in cancer progression, and so is the overexpression of the enzyme phospholipase D (PLD) and its reaction product, phosphatidic acid (PA). However, an understanding of how these signaling molecules interact at the level of gene expression is lacking. Catalytically active PLD enhanced expression of EGFR in human breast cancer cells. Overexpression of the PLD2 isoform increased EGFR mRNA and protein expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…We have also seen in Figures 3, 4 and 5 a greater accumulation of PA in vesicles around the nucleus and that this surge in PA led to an increase in EGFR expression, leading us to investigate the nuclear mechanism by which PA increases EGFR expression. PA localizes to the nucleus and interacts with nuclear receptors [3941]. We have shown previously that PA alters the secondary structure of PPARα [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also seen in Figures 3, 4 and 5 a greater accumulation of PA in vesicles around the nucleus and that this surge in PA led to an increase in EGFR expression, leading us to investigate the nuclear mechanism by which PA increases EGFR expression. PA localizes to the nucleus and interacts with nuclear receptors [3941]. We have shown previously that PA alters the secondary structure of PPARα [41].…”
Section: Resultsmentioning
confidence: 99%
“…Both EGFR and PA are transferred to the nucleus to influence gene expression, and some to the Golgi for recycling/export back out of the cell. PA in the nucleus activates gene expression of several genes including EGFR, as PA is a mitogen [39]. Newly synthesized EGFR is then shuttled through the Golgi to the plasma membrane through vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…The phospholipid 1,2,‐dioleyl phosphatidic acid (DOPA) was purchased from Avanti Polar Lipids (840875P, Alabaster, AL, USA). Lipid preparation was carried out as described previously . Briefly, DOPA was prepared from powder in PBS with 0.5% BSA for a final concentration of 1 mmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…Lipids were added to the cells for a final concentration of 300 nmol/L for 4 hours. Previous reports have shown that this form of PA is cell soluble . Post‐treatment cells were harvested and subjected to quantitative RT‐PCR (qRT‐PCR).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that PA, as the product of phospholipase D (PLD), is critical for cancer cell survival and progression, the activity of which is enhanced in multiple cancer types [7,8]. PA also could be generated by other several metabolic pathways including diacylglycerol kinases (DGKs) and lysophosphatidic acid acyltransferase (LPAAT) [9].…”
Section: Introductionmentioning
confidence: 99%